Analysis and solutions to improve account receivables of traditional trade business of company xyz - Manggolo Putro, Tidar; Herlanto Anggoro, Achmad (The Indonesian Journal of Business Administration, 2016)
Abstract - The company business in traditional trade segment grew at double digit rate. However, it faces an issue of even higher increase rate in its relevant Accounts Receivable (AR). This deteriorating AR performance is therefore an important business issue to be resolved in this project. The research methodology used includes activity observation and interview during sales area visit, and use of company data to measure the impact of the AR loss. To analyze the root cause, several conceptual frameworks are used, such as time value of money, cash conversion cycle, average collection period, and credit management. The research finds out that the causes of the problems include insufficient insightful reports that can trigger actions on the drivers of the AR aging, weak credit worthiness assessment process causing confusion in granting credits, and unclear collection performance system. This research recommends solutions including deployment of more effective reports such as AR loss tree and excess financing dashboard that pinpoints where the issues are and hence the responsible function to follow up. A standard business process of customer creditworthiness assessment has been designed and is proposed to be implemented across all area, and similarly for standard collection process, which differentiates treatment based on the type of the distributors, and include new collection role with clear accountability. Furthermore, ideas on speeding up collection are introduced, consisting of Distributor Financing and Cash Discount improvement. Both schemes rely on discipline execution of the new collection process.Â Keywords: Account Receivable, Collection management, Credit management